Use of cannabidiol for off-label treatment of patients with refractory focal, genetic generalised and other epilepsies - Marie Hollander; Thomas Mayer; Kerstin Alexandra Klotz; Susanne Knake; Felix von Podewils; Gerhard Kurlemann; Ilka Immisch; Felix Rosenow; Susanne Schubert-Bast; Adam Strzelczyk (Neurological Research and Practice)
Abstract Background In randomized controlled trials, add-on cannabidiol (CBD) has been shown to reduce seizure frequency in patients with Lennox-Gastaut syndrome, Dravet syndrome and Tuberous sclerosis complex. Real-world studies provide insights into the drug’s profile in other off-label indications. This study evaluated factors predicting efficacy, retention, and tolerability of add-on CBD used for off-label treatment in clinical practice for patients with refractory focal-onset, genetic generalised, and other unclassified epilepsies. Methods A retrospective cohort study recruiting all patients who had started CBD between 2019 and 2023 for off-label treatment at six German epilepsy centres. Data on baseline and follow-up were obtained from patients’ medical records. Results A total of 108 patients (mean age 27.3; median 36; range 1.4–68 years, 56 male) were treated with CBD. At three months, 42 (38.9% considering all 108 patients that started CBD) reported at least a 50% reduction in seizures, including 28 patients (25.9%) with a 50–74% reduction, and 14 (13%) with a reduction of 75–99%. Among those 48 patients experiencing tonic-clonic seizures (TCS), at least 50% response was reported by 45.8%, and eight (16.7%) patients were free of TCS. Sex, age, epilepsy syndrome, concomitant clobazam (CLB) use, and the number of concomitant or previous ASMs were not predictive of response. Mean seizure days per month significantly decreased from a mean of 16.8 (median: 13.5) to 14.5 (median 10, p = 0.002). The probability of patients remaining on CBD treatment was 85.2% (n = 92/108, 16 discontinuations) at three months, 73.5% at six months and 61.1% at twelve months; retention was better in children or adolescents compared to adults (log-rank p = 0.014). Using the CGI-C for overall impression, 69 (63.0%) patients were rated as very much, much, or minimally improved; for behaviour, 60 (55.6%) reported within this range of improvement. TEAEs were reported in 41 (38%) patients. The most frequent were diarrhoea (n = 15), sedation (n = 13), and nausea and vomiting (n = 7). Conclusions Our results suggest CBD to be an effective ASM, with 50% responder rates similar to those observed in regulatory trials for other ASMs licensed in focal epilepsies. Its off-label use in refractory focal-onset, genetic generalised, and other unclassified epilepsies seems to be safe and well-tolerated.